Important skills in a period of stress. experience of teaching a group stress management course for adults self-help+ (self-help+) - Naumenko Галина; Zhuk Алла; Янчук, Тетяна (Psychosomatic Medicine and General Practice, 2023)
Relevance. The full-scale war on the territory of Ukraine resulted in severe and long-lasting distress among its population. The distress caused by the hostilities may cause a psychological trauma among Ukrainians. [1] According to experts of the World Health Organization, one of the consequences of the military actions taking place in Ukraine is the emergence of mental health problems. [2] This may affect a quarter of the country’s population, namely, according to Yarno Gabiht, a representative of the above mentioned organization, the number will approach 10 million. Moreover, mental disorders can be displayed in different ways: starting from manifestations of anxiety and ending with more severe conditions. [2] Talking about "more severe conditions", the concept of post-traumatic stress disorder is meant. The above-mentioned representative of the WHO also pointed to the fact that the number of those applying for the help concerning the described problem after the end of the 10-month period from the beginning of the invasion of Russian troops has increased. [2] WHO experts have developed a number of short-term scalable psychological interventions, one of which is a group stress management course for adults, Self-Help Plus (SH+). SH+ consists of pre-recorded audios and an illustrated “Essential Stress Skills” manual that could be used by participants for individual skill development. [3; 4] This group stress management course for adults offers a range of psychological exercises aimed at mastering stress management skills. The exercises, presented in the form of illustrations and short comments, show equal effectiveness both in conditions of active hostilities and in peaceful communities, among persons who have been diagnosed with or not diagnosed with a mental disorder. Working according to the instructions of the manual, the facilitator (assistant) together with the co-facilitator teach stress management skills to people who have been affected by adverse circumstances. [3; 4] It should be noted that Self-Help Plus is not psychotherapy or psychological counseling, or a substitute for more specialized services. This guideline is evidence-based, requires fewer resources to implement, is short-term and reduces time to provide help, and provides skills that can be useful when access to psychosocial service providers is absent or limited, and those are the essential advantages of this course. Also, one of the key tasks of short-term interventions is the redistribution of the burden between informal organizations, medical workers and experts in the field of mental health. [5] The goal of the work was to help people learn how to cope with stress in adverse life circumstances. Methods. 20 people agreed to participate in the Self-Help Plus course: 16 women and 4 men, aged 24-67. For the experimental study, the questionnaire "Coping strategies of R. Lazarus", the reactive and personal anxiety scale of C. D. Spielberger - Y. L. Khanin (STAI), the Hospital Anxiety and Depression Scale (HADS) and the method of mathematical processing of the criterion by T.Student were used for the experimental study. The results. With the help of R. Lazarus’s "Coping strategies" questionnaire, it was found that a significant part of the participants, which is 60%-80%, shows maladaptive behavior, which is expressed through coping strategies: confrontation, distancing and escape. According to the results of the Ch.D. Spielberger-Y.L. Khanin scale of reactive and personal anxiety (STAI), the level of reactive anxiety decreased in the studied group. A repeat survey on the Hospital Anxiety and Depression Scale (HADS) showed signs of reduction in mood disorder to moderate/mild state or no disorder at all. In the course of the study, it was found out that most participants of the Self-Help Plus (SH+) course developed stress management skills. According to the Student’s formula, the Student’s t-criterion of 2.09 was obtained, which makes the probability of an error-free forecast about 95%.